Pembangunan antena lubang alur untuk aplikasi capaian wayarles berjalur lebar tetap pada frekuensi 5725-5875mhz - Mohd. Ibrahim, Imran (2005)
Nowadays, Wireless Local Area Network (WLAN) become more popular due to its capability to carry high speed signal and it is cost saving. In this system, antenna plays a significant role in building effective communication between places at different location. Radial Line Slot Array Antenna (RLSA) has been designed and developed based on IEEE 802.11a standard in the frequency range of 572-5875MHz for WLAN system applications. Typically this system uses standard parabolic dish antenna. However the use of these antennas has some disadvantages such as aperture blockage. To overcome this drawback, a new antenna design is proposed and investigated. Therefore, this research was conducted in order to design and develop an antenna with aesthetic, low cost, high performance, durable and flat. The development of linearly polarized RLSA antenna with experimental performance is presented. The RLSA was constructed base on beam squinted design. The prototype development processes included specification definition, selection of the dielectric material and construction of prototype. The production of prototypes is divided into three stages. The first stage is to produce the first prototype and to evaluate its performance. The second stage is to investigate and improve the performance of the prototypes. Finally the last stage is to produce the final prototype with the capability to apply on WLAN system. This project has successfully produced antenna in range 5725-5875 MHz with minimum return loss 11dB, the antenna gain is 26 dB, antenna bandwidth is 12% with radiation efficiency 63% and validated its potential to be operated on WLAN system.